Optimizing Mushroom Cultivation for SMEs: Development of a Frugal Innovation-Based IoT-Enabled Smart Kumbung System - Kawuryan Renita; Pratiwi Sari; Kandang Tandi; Anthama Lintang Putra; Nurramadani Alifia (E3S Web of Conferences)
This study addresses the current challenges in traditional mushroom cultivation, including inconsistent yields, high production costs, and environmental vulnerabilities hindering small and medium enterprises (SMEs). The research formulates an Internet of Things (IoT)-enabled "Smart Kumbung" system, adhering to frugal innovation principles, to enhance mushroom cultivation procedures. The Smart Kumbung system integrates IoT technology to monitor and control key environmental parameters such as temperature and humidity. It includes IoT sensors for real-time monitoring, a misting system for humidity regulation, automatic lighting controlled by photoelectric sensors, and a smartphone interface for remote operation. The prototype was designed using cost-effective, sustainable materials and tested over a two-month cultivation period to evaluate its functionality. Field tests demonstrated the system's ability to maintain optimal temperature (24–26°C) and humidity levels (85%), improving productivity and reducing resource consumption. The system achieved significant water and energy efficiency while ensuring user- friendliness, with local farmers expressing high satisfaction. This research highlights the potential of IoT and frugal innovation to empower SMEs, improve agricultural sustainability, and enhance food security. The findings apply to sustainable agriculture, SME development, and technological innovation for resource-limited communities.